Tecnologia de aproveitamento da água de chuva na comunidade rural Lagoa de Dentro em Doutor Severiano-RN - Ferreira, Maria Analine (Universidade Federal Rural do Semi-Árido, 2019)
Water scarcity will affect two thirds of people in the world by 2050. Life can not be imagined without water. This means that technologies for the utilization of the rain water such as cistern systems, especially in rural communities have gained more prominence, in some more extreme cases, become the only source of water supply, as the example in the Brazilian Northeast, where droughts occur regularly, characterizing the region as a "drought polygon", which means that the population is always looking for ways to adapt to the way of living, planting and raising animals according to the rainfall and the type of soil that they have. As a result, this work aims to undertake a survey of the main types of cisterns and their specifications for construction in the rural community of Lagoa de Dentro, located at Doutor Severiano/RN, where the battle for access to water is a harsh reality. For the determination of tank capacity (volume), a pattern was taken, by using data from the roof areas of five residences and daily precipitation. These data obtained by Agricultural Research Agency from Rio Grande do Norte - EMPARN, which were later used to estimate the annual average, by means of a spreadsheet Excel software in the period from 1964 to 2018. Then the calculation of the average of all days without rain during the mentioned period, associated with the individual water demand of the houses, allowed the correct sizing to make water available at the point of precision. The results show the insufficiency of the cisterns of 16 thousand liters installed to capture all the volume of the rain due to the estimated average precipitation of 785.91 mm / year and the need of the rural families to obtain an adequate dimensioning to meet their primary needs as also reinforce the pedagogical character, the act of educating people about the responsible use of water, and the importance of using this precious resource with wisdom and moderation.
Technology for harnessing rainwater in the rural community Lagoa de Dentro in Doutor Severiano-RN
Monografia
Keywords: Precipitação média; Volume das chuvas; Escassez de água; Average precipitation; Rain volume; Water scarcity; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA